Implementasi Program Keberagaman Dalam Mengembangkan Akhlak Karimah Peserta Didik - Sumarna Sueb; Cece Hidayat; Ujang Hermawan (STAI Al-Mas'udiyah, 2024)
This research employs a descriptive qualitative approach using a literature review method to examine the implementation of diversity programmes in developing the moral character of students within Islamic education contexts. The study aims to explore how diversity initiatives can be effectively integrated into educational curricula and extracurricular activities to foster inclusivity and respect for differences among students. By analysing various primary and secondary sources, including books, journals, and scholarly articles, the research identifies key themes and challenges associated with implementing these programmes. The findings are intended to provide comprehensive insights into the effectiveness of diversity programmes in enhancing students' moral character and offer recommendations for educators and policymakers on best practices. This approach allows for an in-depth understanding of how Islamic values can be incorporated into educational strategies to promote a more inclusive and ethically grounded learning environment. The study contributes valuable perspectives on the role of diversity in moral development within the framework of Islamic education.